Development of an instrument for the evaluation of distance education modules in the health area (Research, Society and Development, 2021)
Introduction: Information and communication technologies gain space in the teaching and learning processes, mainly in the form of modules and distance courses and have become important in the training of health professionals. Objective: To develop an instrument for the evaluation of educational modules mediated by technology for permanent health education. Methodology: This is an exploratory descriptive study that started from a systematic review and based on its results, the instrument for the evaluation of educational modules was constructed for later validation. Results: the developed instrument allows to identify the characterization of the course and to evaluate the strategies, educational resources and pedagogical dimensions, in addition to the quality assessment, characterization of the evaluator and other important information for the process of construction of educational modules for the health area. Conclusion: It is intended, from this instrument and after validated, to contribute to the evaluation of distance courses and modules in the health area, thus offering greater quality in the teaching / learning processes.